Information in a Local and Global Context - Quan-Haase, Anabel; Rubin, Victoria L.; Chaves, Debbie (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2014)
Proceedings of the CAIS/ACSI 2012 conference.